2011
DOI: 10.1007/s13580-011-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

Internal transcribed spacer (ITS) and genetic variations in Lilium native to Korea

Abstract: Internal transcribed spacers (ITS) of nuclear ribosomal DNA cistrons were studied in wild Lilium species native to Korea and compared with those species in the genus distributed in other countries to investigate the phylogenetic relationships among Lilium species. Sequence analysis data of Lilium plants collected from China and Japan were also included to study the inter-and intra-specific relationships in the genus. Lilium species formed a monophyletic clade and were separated in two clusters that belonged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In our IRAP analysis, the Martagon lilies formed an out-group cluster to support the Lighty's proposal (Lighty 1968(Lighty , 1969. Sequence variation in the internal transcribed spacers (ITS) of rDNA also showed the Martagon lilies were in the out-group to other lilies that are growing in Korea (Sultana et al 2011). Among the Sinomartagon lilies, the out-grouping of L. lancifolium from other Asiatic lilies is also interesting.…”
Section: Discussionmentioning
confidence: 99%
“…In our IRAP analysis, the Martagon lilies formed an out-group cluster to support the Lighty's proposal (Lighty 1968(Lighty , 1969. Sequence variation in the internal transcribed spacers (ITS) of rDNA also showed the Martagon lilies were in the out-group to other lilies that are growing in Korea (Sultana et al 2011). Among the Sinomartagon lilies, the out-grouping of L. lancifolium from other Asiatic lilies is also interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Information of ITS sequences has been published for different L . callosum populations collected from Japan (Dubouzet and Shinoda 1999 ; Nishikawa et al 1999 , 2001 ), South Korea (Sultana et al 2011 ; Lee et al 2011 ), and China (Du et al 2014 ). Sequence-related amplified polymorphism (SRAP) markers (Li et al 2011 ) and rbcL and matK gene sequences were also used to analyze phylogenetic relationships between Lilium species, including L .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with different origins of L . callosum , plants from Korea, Japan and China were placed into different groups, and this may be attributed to the considerable divergence in lengths and sequences of ITS1 and ITS2 (Sultana et al 2011 ). Pelkonen and Pirttilä ( 2012 ) also constructed a phylogenetic tree of the main species and sections of the Lilium .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular marker studies in Lilium are not advanced compared to other plant species because of their large genome sizes. Molecular studies of wild Lilium species has been increasing and the reported molecular markers are ISSR (Xi et al 2012), SRAP (Robarts and Wolfe 2014), RAPD (Huang et al 2009), and ITS (Kumari et al 2018;Sultana et al 2011) to explore diversity of wild Lilium species. So, molecular techniques are required to systematically study of wild Lilium species in depth.…”
Section: Introductionmentioning
confidence: 99%